Requirements for an ubiquitous computing infrastructure - Maffioletti, S. (Культура народов Причерноморья, 2001)
Ubiquitous computing is an emerging paradigm for interactions between people and computers. Its aim is to break away from the desktop computing to provide computational services to a user when and where required. In this paper we present the design criteria for an infrastructure platform for ubiquitous computing applications. The motivation for building such infrastructure is to formalize a common design methodology for developing application based on the notion of Interactive Environment.